2011
DOI: 10.1103/physrevb.84.081301
|View full text |Cite
|
Sign up to set email alerts
|

Energy shift and wave function overlap of metal-organic interface states

Abstract: The properties of Shockley-type interface states between π -conjugated organic molecular layers and metal surfaces are investigated by time-resolved two-photon photoemission experiments and density functional theory. For perylene-and naphthalene-tetracarboxylic acid dianhydride (PTCDA and NTCDA) adsorbed on Ag(111), a common mechanism of formation of the interface state from the partly occupied surface state of the bare Ag (111) is revealed. The energy position is found to be strongly dependent on the distance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
70
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 23 publications
9
70
0
Order By: Relevance
“…[3] reveal that outside the surface, where STM and STS are measured, the IS indeed exhibits a density distribution that clearly reflects its hybridization with the molecular orbitals. Moreover, Marks et al [5] find that, in agreement with the original conjecture of ref. [1], the bending of the carboxylic oxygen atoms towards the Ag(111) surface enhances the molecular overlap with the up-shifted surface state.…”
Section: A Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…[3] reveal that outside the surface, where STM and STS are measured, the IS indeed exhibits a density distribution that clearly reflects its hybridization with the molecular orbitals. Moreover, Marks et al [5] find that, in agreement with the original conjecture of ref. [1], the bending of the carboxylic oxygen atoms towards the Ag(111) surface enhances the molecular overlap with the up-shifted surface state.…”
Section: A Introductionsupporting
confidence: 77%
“…The interface to the metallic leads is one of them, as it constitutes the link between two electronic sub-units with very different properties; discrete molecular levels, on the one hand, meet the continuum band structure of an inorganic solid, on the other. The layer in direct contact to the substrate (contact primer layer) thereby plays a decisive role, determining the electronic structure at these interfaces, and it has been found that distinct interface states (IS) may form as a result of the nearby molecular layer [1][2][3][4][5].…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect has also been reported for pure PTCDA adsorbed on Ag(1 1 1) [61,71] and discussed in terms of a so called interface state (IS), originating from the well known Ag(1 1 1) surface state which becomes depopulated due to the adsorption of PTCDA [13,72]. For PTCDA/Ag(1 1 1) the IS is located at (0.570 ± 0.030) eV [72] and contains contributions of the LUMO+1 and LUMO+2 levels, as revealed by DFT [73]. Hence, the question arises whether the IS of the MBW structure also exhibits some density of states of the unoccupied molecular orbitals, apparently of both molecules.…”
Section: Scanning Tunneling Spectroscopymentioning
confidence: 58%
“…13,14 As was observed by the 2PPES in Ref. 15, in the case of the so-called relaxed ordered NTCDA ML adsorbed on the Ag(111) surface, there is also an unoccupied Shockley-type interface state. The latter has smaller energy than that in the case of the PTCDA ML.…”
Section: Introductionmentioning
confidence: 60%